1975
DOI: 10.1515/zna-1975-1113
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in the Alkali C1 —n. C4 Alkanoates

Abstract: The enthalpies and entropies of fusion and of solid state transitions in Li formate and acetate; Li, Na, K, Rb, Cs propionates; Li, Rb, Cs n.butyrates were determined by differential scanning calorimetry. Supplementary information was provided through conductance measurements on solids. The collected data, together with those from previous papers, allowed to give a picture of the thermal behaviour of the alkali C1-n. C4 alkanoates. Heat capacity data on solid and molten Na formate, acetate and propionate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
29
1

Year Published

1980
1980
1999
1999

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 0 publications
14
29
1
Order By: Relevance
“…in the temperature range (280 to 310) K with a Perkin-Elmer DSC-2 apparatus calibrated for temperature and enthalpy at both superambient and subambient temperatures. (20,21) However, this calibration procedure has been recently improved as described in reference 13. In particular: benzoic acid in the form of pressed pellets was used as a calorimetric standard over the whole experimental temperature range; a (0.10He + 0.90Ne) mixture (He mass fraction 0.999995 and Ne mass fraction > 0.9998) supplied by SIAD (Dalmine, Bergamo, Italy) was employed as a more TABLE 1.…”
Section: Methodsmentioning
confidence: 99%
“…in the temperature range (280 to 310) K with a Perkin-Elmer DSC-2 apparatus calibrated for temperature and enthalpy at both superambient and subambient temperatures. (20,21) However, this calibration procedure has been recently improved as described in reference 13. In particular: benzoic acid in the form of pressed pellets was used as a calorimetric standard over the whole experimental temperature range; a (0.10He + 0.90Ne) mixture (He mass fraction 0.999995 and Ne mass fraction > 0.9998) supplied by SIAD (Dalmine, Bergamo, Italy) was employed as a more TABLE 1.…”
Section: Methodsmentioning
confidence: 99%
“…In the latest paper of this seriesc3' it was shown inter a&a that for potassium propanoate CH,CH,CO,K the phase stable in the lowest temperature range (crystal III) goes to an isotropic liquid through the steps: (4) from the melt region down to about 100 K proved that the next higher linear homolog: potassium butanoate, CH,CH,CH,CO,K, undergoes a much more complicated "stepwise melting process" implying the phase relations: The peculiarities made evident by d.s.c. suggested that a more detailed investigation of the thermophysics of the isomeric butanoates of potassium was advisable, in order (i) to get information (so far completely missing) on the behavior of 2-methylpropanoate in the sub-ambient region, and (ii) to provide adiabatic equilibrium heat capacities as complete as possible for both butanoate and 2-methylpropanoate.…”
Section: Introductionmentioning
confidence: 99%
“…Both the Fa and Ff values, as well as the corresponding AS's decrease smoothly with increasing nc . Least-squares fitting gave the fusion of CsC5-CsC20 from [2] and this work; curve 2 (hand-drawn): clearing of CsC6-CsC20 from [2] and this work; curves 3 and 4: fusion and clearing, respectively of RbC5-RbC20 according to [7,8], nr = 7 n, = 6 nr = 7 n,=8 The data from Table 2 and those from [1,2] allow one to outline the boundaries of the liquid crystal region in the series of the linear cesium soaps from CsC6 (which is the lowest homolog exhibiting a mesomorphic liquid phase) to CsC20, as shown in Fig. 3, where the Ff for CsCs [2] and the Fcfs and Ff's from the literature are also reported.…”
Section: Introductionmentioning
confidence: 94%
“…Previous DSC work in this laboratory [1,2] dealt with phase relationships in cesium linear alkanoates up to dodecanoate. In particular, it was shown that starting with hexanoate the stepwise melting process -a peculiarity of so many alkali soaps -leads to the formation of a liquid crystalline phase before the isotropic liquid state is reached.…”
Section: Introductionmentioning
confidence: 99%